Hopefulness During COVID-19: Associations With Function, Sleep, and Loneliness in the NHATS. (17th December 2021) - Hladek, Melissa; Li, Qiwei; Samuel, Laura; Drazich, Brittany; Cudjoe, Thomas; Szanton, Sarah
Abstract: The associations between hopefulness and function, loneliness, and sleep have not been explored in a nationally representative sample of older adults. Additionally, COVID19 dramatically increased stress burden, potentially influencing these relationships. This study used National Health and Aging Trends COVID19 Supplement data (N=2, 894 adults aged ≥ 65 years) to evaluate cross-sectional associations between hopefulness about the future during COVID19 with limitations in activities of daily living (ADLs) using a negative binomial model and one-item sleep and loneliness measures using ordered logistic models. Adjusting for age, race/ethnicity, and education and applying sampling weights, increased hopefulness was associated with better ADLs (b= -0.11, p-value=0.021), less loneliness (b=-0.32, p-value=<0.001), and better sleep (b= -0.27, p-value= <0.001). In the midst of a world-wide stressor, hopefulness was associated with better function and symptoms. This relationship is likely bidirectional and further longitudinal research is needed.